Do alternative irrigation strategies for rice cultivation decrease water footprints at the cost of long-term soil health? - John Livsey; Thomas Kätterer; Giulia Vico; Steve W Lyon; Regina Lindborg; Anna Scaini; Chau Thi Da; Stefano Manzoni (Environmental Research Letters, 2019)
The availability of water is a growing concern for flooded rice production. As such, several water-saving irrigation practices have been developed to reduce water requirements. Alternate wetting and drying and mid-season drainage have been shown to potentially reduce water requirements while maintaining rice yields when compared to continuous flooding. With the removal of permanently anaerobic conditions during the growing season, water-saving irrigation can also reduce CO _2 equivalent (CO _2eq ) emissions, helping reduce the impact of greenhouse gas (GHG) emissions. However, the long-term impact of water-saving irrigation on soil organic carbon (SOC)—used here as an indicator of soil health and fertility—has not been explored. We therefore conducted a meta-analysis to assess the effects of common water-saving irrigation practices (alternate wetting and drying and mid-season drainage) on (i) SOC, and (ii) GHG emissions. Despite an extensive literature search, only 12 studies were found containing data to constrain the soil C balance in both continuous flooding and water-saving irrigation plots, highlighting the still limited understanding of long-term impacts of water-saving irrigation on soil health and GHG emissions. Water-saving irrigation was found to reduce emissions of CH _4 by 52.3% and increased those of CO _2 by 44.8%. CO _2eq emissions were thereby reduced by 18.6% but the soil-to-atmosphere carbon (C) flux increased by 25% when compared to continuous flooding. Water-saving irrigation was also found to have a negative effect on both SOC—reducing concentrations by 5.2%—and soil organic nitrogen—potentially depleting stocks by more than 100 kg N/ha per year. While negative effects of water-saving irrigation on rice yield may not be visible in short-term experiments, care should be taken when assessing the long-term sustainability of these irrigation practices because they can decrease soil fertility. Strategies need to be developed for assessing the more long-term effects of these irrigation practices by considering trade-offs between water savings and other ecosystem services.